Mild traumatic brain injuries with minor intracranial hemorrhage: Can they Be safely managed in the community? – A cohort study. (April 2020) - Gupta, Sanjay; Kaafarani, Haytham M.A.; Fagenholz, Peter J.; Tabrizi, Myriam; Rosenthal, Martin; El Hechi, Majed W.; Velmahos, George C.
Abstract: Background: Patients with mild traumatic brain injury (mTBI) are frequently transferred to level 1 trauma centers (L1TC) if they have minor findings on a computerized tomographic scan of the head due to the absence of continuous neurosurgical coverage in community hospitals (CH). We hypothesized that such patients can be safely managed at community hospitals with a qualified Trauma team. Methods: This is a multicentered Retrospective Cohort Study. Patients with mild Traumatic Brain Injury (defined as Glasgow Coma Scale [GCS] 13–15 at presentation) and with minor findings on head Computerized Tomography (CT) presenting at a L1TC or 4 Community Hospitals between March 1st, 2012 and February 28th, 2014 were included. All these community hospitals are Level III Trauma center with a well-organized trauma team. Minor CT findings were defined as 1) epidural hematoma<2 mm; 2) subarachnoid hemorrhage<2 mm; 3) subdural hematoma<4 mm; 4) intraparenchymal hemorrhage<5 mm; 5) minor pneumocephalus; or 6) linear or minimally depressed skull fracture. Our primary end point was the need for TBI specific interventions in 3 groups of patients: 1) direct admission to the L1TC (L1TC group), 2) those admitted at one of the 4 CH (CH group), and 3) those transferred from CH to L1TC (TRANSFER group). TBI-specific interventions were defined as intracranial pressure monitor (ICP) placement, hyperosmolar therapy, or neurosurgical operation. Our secondary aim was to demonstrate that these patients can be safely managed in Community Hospitals with qualified Trauma teams. We also sought to identify the clinical outcomes in these three groups of patients – in terms of mortality and complications. Results: A total of 191 patients were included - 39 CH, 64 L1TC and 88 TRANSFER. There was no difference among the groups in terms of TBI-specific interventions: one TRANSFER, four L1TC, and no CH patients required hyperosmolar therapy (p = 0.277). None of the patients required placement of an intracranial pressure monitoring device (ICP) or a neurosurgical operation and complications and mortality rates were similar among the groups. Conclusions: Patients with mild TBI and minor findings on head CT can be safely managed at CH with qualified Trauma Teams. Level of evidence: Therapeutic/Care Management Study, Level IVhbv. Highlights: Combination of physiologic function (GCS 13–15) and anatomic information (minor head CT findings) identifies patients with mild TBIs, who can be safely managed by acute care surgeons at Community Hospitals. Minor CT findings were defined as: 1) an epidural hematoma less than 2 mm thick, 2) subarachnoid hemorrhage measuring less than 2 mm, 3) subdural hematoma less than 4 mm thick, 4) intraparenchymal hemorrhage measuring less than 5 mm, 5) minor pneumocephalus defined as 2–3 small bubbles of air, or 6) linear or minimally depressed skull fracture. Repeat head CT in patients with stable neurologic examination does not change management.